Reproduction of East-African bats may guide risk mitigation for coronavirus spillover - Diego Montecino-Latorre; Tracey Goldstein; Kirsten Gilardi; David Wolking; Elizabeth Van Wormer; Rudovick Kazwala; Benard Ssebide; Julius Nziza; Zikankuba Sijali; Michael Cranfield; PREDICT Consortium; Jonna A. K. Mazet (BMC, 2020)
Abstract Background Bats provide important ecosystem services; however, current evidence supports that they host several zoonotic viruses, including species of the Coronaviridae family. If bats in close interaction with humans host and shed coronaviruses with zoonotic potential, such as the Severe Acute Respiratory Syndrome virus, spillover may occur. Therefore, strategies aiming to mitigate potential spillover and disease emergence, while supporting the conservation of bats and their important ecological roles are needed. Past research suggests that coronavirus shedding in bats varies seasonally following their reproductive cycle; however, shedding dynamics have been assessed in only a few species, which does not allow for generalization of findings across bat taxa and geographic regions. Methods To assess the generalizability of coronavirus shedding seasonality, we sampled hundreds of bats belonging to several species with different life history traits across East Africa at different times of the year. We assessed, via Bayesian modeling, the hypothesis that chiropterans, across species and spatial domains, experience seasonal trends in coronavirus shedding as a function of the reproductive cycle. Results We found that, beyond spatial, taxonomic, and life history differences, coronavirus shedding is more expected when pups are becoming independent from the dam and that juvenile bats are prone to shed these viruses. Conclusions These findings could guide policy aimed at the prevention of spillover in limited-resource settings, where longitudinal surveillance is not feasible, by identifying high-risk periods for coronavirus shedding. In these periods, contact with bats should be avoided (for example, by impeding or forbidding people access to caves). Our proposed strategy provides an alternative to culling - an ethically questionable practice that may result in higher pathogen levels - and supports the conservation of bats and the delivery of their key ecosystem services.